College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter 1 - Equations and Inequalities - Exercise Set 1.2 - Page 118: 50



Work Step by Step

$\dfrac{6}{x+3}-\dfrac{5}{x-2}=\dfrac{-20}{x^{2}+x-6}$ Factor the denominator of the fraction on the right side: $\dfrac{6}{x+3}-\dfrac{5}{x-2}=\dfrac{-20}{(x+3)(x-2)}$ Multiply the whole fraction by $(x+3)(x-2)$: $(x+3)(x-2)\Big[\dfrac{6}{x+3}-\dfrac{5}{x-2}=\dfrac{-20}{(x+3)(x-2)}\Big]$ $6(x-2)-5(x+3)=-20$ $6x-12-5x-15=-20$ Take all terms without $x$ to the right side of the equation, simplify and solve for $x$: $6x-5x=-20+15+12$ $x=7$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.